Assessment of genetically modified maize MON 87411 for food and feed uses, import and processing, under Regulation (EC) No 1829/2003 (application EFSA‐GMO‐NL‐2015‐124). (28th June 2018) - ,; Naegeli, Hanspeter; Birch, Andrew Nicholas; Casacuberta, Josep; De Schrijver, Adinda; Gralak, Mikołaj Antoni; Guerche, Philippe; Jones, Huw; Manachini, Barbara; Messéan, Antoine; Nielsen, Elsa Ebbesen; Nogué, Fabien; et al.
Abstract: Maize MON 87411 was developed to confer resistance to corn rootworms ( Diabrotica spp.) by the expression of a modified version of the Bacillus thuringiensis cry3Bb1 gene and a DvSnf7 dsRNA expression cassette, and tolerance to glyphosate‐containing herbicides by the expression of a CP4 5‐enolpyruvylshikimate‐3‐phosphate synthase ( cp4 epsps ) gene. The molecular characterisation data and bioinformatics analyses did not identify issues requiring assessment for food and feed safety. No statistically significant differences in the agronomic and phenotypic characteristics tested between maize MON 87411 and its conventional counterpart were identified. The compositional analysis of maize MON 87411 did not identify differences that required further assessment except for palmitic acid levels in grains from not treated maize MON 87411. The GMO Panel did not identify safety concerns regarding the toxicity and allergenicity of the Cry3Bb1 and CP4 EPSPS proteins, as expressed in maize MON 87411 and found no evidence that the genetic modification might significantly change the overall allergenicity of maize MON 87411. The nutritional impact of maize MON 87411‐derived food and feed is expected to be the same as those derived from the conventional counterpart and non‐GM commercial reference varieties. The GMO Panel concludes that maize MON 87411, as described in this application, is nutritionally equivalent to and as safe as the conventional counterpart and the non‐GM maize reference varieties tested, and no post‐market monitoring of food/feed is considered necessary. In the case of accidental release of viable maize MON 87411 grains into the environment, maize MON 87411 would not raise environmental safety concerns. The post‐market environmental monitoring plan and reporting intervals are in line with the intended uses of maize MON 87411. The GMO Panel concludes that maize MON 87411, as described in this application, is as safe as its conventional counterpart and the tested non‐GM maize reference varieties with respect to potential effects on human and animal health and the environment.